ENTREPRENEURSHIP RESTORATION AND DEVELOPMENT IN UKRAINE ON THE ESG-CONCEPT BASIS - Gura, V.; Berdanova, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The article examines the evolution of conceptual views on the sustainable development of the planetary system from the theory of the noosphere by V.I. Vernadsky to the modern paradigm of sustainable development of society. The essence of the global goals of sustainable development until 2030, which reflect the scale and direction of the new agenda of mankind, is revealed. It is determined that the ESG-concept is a practical tool for the participation of the business sector in achieving the goals of sustainable development. The urgency of responsible activity of business structures for the restoration of public life in Ukraine in the postwar period is emphasized. The main aspects of ESG-concept as an environmental, social, and management triangle of the formation of sustainable viability of enterprises are highlighted. The positive impact of environmental and social risk management on the long-term market value of companies is substantiated. It is determined that the main driving forces of the implementation of ESG-principles in the private sector, include investors, international organizations, international banks of development, governments, consumers. The application of the ESG-principles in Ukraine on the example of the ESG-strategy until 2030 of the DTEK Group is studied, and their priorities for participation in achieving the goals of sustainable development are highlighted. The main directions of activity of socially responsible domestic enterprises are determined: labor relations, environmental responsibility, consumer relations, community development, and anti-corruption practices. It is proved that the disclosure of non-financial information and ensuring the transparency of companies' activities is another new process in Ukraine, which is complicated by the lack of generally accepted standards for non-financial information disclosure. The article identifies the main problems of wide application of ESG-concept in the practical activities of the business sector and substantiates the directions of intensification of this process, including: leadership and strengthening the influence of large companies on the implementation of economic agents ESG-principles; implementation of socially responsible investment by financial structures; standardization of the content and process of disclosure of non-financial information; popularization and explanation of the essence and role of ESG-concepts for the development of the business sector; training of competent specialists in this field.
Keywords: sustainable development, global goals of sustainable development, ESG-concept, ESG-strategy, socially responsible investment